Harnessing floating solar power to decarbonize Southeast Asia’s energy sector for carbon neutrality - Goh, Kai Chen; Tonni Agustiono, Kurniawan; Khurmatbek, Jumaniyozov; Abdelkader, Anouzla; Faissal, Aziz; Ngoh, Wan Fei; Kasim Sakran, Abass; M. Imran, Khan; Dongdong, Zhang; Toh, Tien Choon; Gui, Hun Chuen; Chong, Wan Siang; et al. (Elsevier Ltd., 2026)
Floating photovoltaics (FPV) represent a cutting-edge solution for sustainable energy generation in Southeast Asia, a region characterized by abundant water resources and high solar irradiance. This work delves into the potential of FPV in decarbonizing the energy sector, highlighting its dual role in generating clean energy and mitigating water evaporation. With an estimated 300 MW of FPV capacity addition by early 2024, Southeast Asia is set to make significant strides in reducing greenhouse gas (GHG) emissions, aligning with global efforts to combat climate change. The FPV potential in the region is impressive, with Vietnam containing around 21–46 GW in reservoirs and 21–54 GW in natural water bodies alone. The work highlights the role of FPV in strengthening energy security and fulfilling obligations to the 2015 Paris Climate Agreement. FPV integration within the energy mix may help Southeast Asia cut down fossil fuel dependency, and through this, energy transition to a sustainable economy and greener environment can be achieved. The study also focuses on FPV’s environmental aspects of functioning as an ecosystem, arguing that these systems can improve land-based andbased generation efficiency by about 15 % and decrease water evaporation by 25 %. Recommended policies include setting appropriate incentive and disincentive structures, advancing support for R&D, and promoting cross-agency collaboration for FPV adoption to accelerate decarbonization goals. This work concludes that proper policy settings and government support can enable FPV technologies to enhance the renewable energy strategy for Southeast Asia, thereby contributing to global climate change mitigation.